The Concept of Family Education According to Q.S Lukman: 13-19 - Elfan Fanhas Fatwa Khomaeny (International Consortium of Education and Culture Research Studies, 2017)
Human Being is created by Allah in a state of not knowing anything, but equipped with the senses and minds as tools to be able in receiving knowledge, and also established the concepts and norms which forms the basis of educational process. The occurrence of moral decadence in Indonesian young generation is always associated with the bad education system used, so it is need a systematic and comprehensive effort to understand the nature of human beings and how to educate them based on the references from Allah as the creator. Al-Qur'an gives many examples of good educational process, such as contained in Q.S. Lukman: 13-19. To understand about the educational process can be used a bayani method which includes: identifying the nash of al-qur`an to be studied, identifying the corresponding Nash of Al Qur’an, and understanding the Nash of Al Qur’an textually and contextually. By using Bayani method, the concept of family education based on Q.S Lukman: 13-19, as follows: introducing Allah as a creator and the origin of human being, teaching science as the basis of argumentation, introducing the law of causality (Cognitive aspect), training and making habitual on praying and Amar maruf nahi munkar (Psychomotor aspect), training the patience, caring for others, humble, modest life, and politeness (Affective aspect). The affective aspect in the concept of family education based on Q.S Lukman: 13-19 is dominant about 45.46%, if this concept is used by parents in educating their children, the problem of moral decadence in this country can be minimized.